Anti-freezing solar heat collection plate core for water heater - GUANGPING MA (2000)
The utility model relates to an anti-freezing heat collection plate core for a solar water heater, which is composed of an upper circulating pipe, a lower circulating pipe, a heat collection pipe arranged between the upper and the lower circulating pipes and vanes, wherein, both ends of the upper and the lower circulating pipes are made into circular pipe orifices, and the middle part is provided with pipes having other shapes excepting the circular shape, such as prismatic pipes, square pipes, elliptical pipes, triangle pipes, semicircular pipes, pentagonal pipes, etc. When water in the upper and the lower circulating pipes is frozen, the pipes can generate corresponding deformation to increase volume, so the problem that the upper and the lower circulating pipes are swelled to be broken for the stored water is frozen. The utility model is particularly suitable for being used in the areas where the temperature is little subzero in the south of China.